Valorization of waste biomass for synthesis of carboxy-methyl-cellulose as a sustainable edible coating on fruits: A review - Dey, Puspita; Bhattacharjee, Satyajit; Yadav, Dev Kumar; Hmar, Baby Zaithanpuii; Gayen, Kalyan; Bhowmick, Tridib Kumar (International journal of biological macromolecules, 2023)
The coating on fruits and vegetables increases the shelf-life by providing protection against their spoilage. The existing petroleum-based coating materials have considerable health threats. Edible coating materials prepared with the cellulose derivative extracted from the waste biomass could be a sustainable alternative and environment friendly process to increase the shelf-life periods of the post-harvested crops. Selection of suitable waste biomass and extraction of cellulose are the critical steps for the synthesis of cellulose based edible film. Conversion of extracted cellulose into cellulosic macromolecular derivatives such as carboxy-methyl-cellulose (CMC) is vital for synthesizing edible coating formulation. Applications of sophisticated tools and methods for the characterization of the coated fruits would be helpful to determine the efficiency of the coating material. In this review, we focused on: i) criteria for the selection of suitable waste biomass for extraction of cellulose, ii) pretreatment and extraction process of cellulose from the different waste biomasses, iii) synthesis processes of CMC by using extracted cellulose, iv) characterizations of CMC as food coating materials, v) various formulation techniques for the synthesis of the CMC based food coating materials and vi) the parameters which are used to evaluate the shelf-life performance of different coated fruits. [Display omitted] •Selection of cellulosic waste material for edible coating on fruits and vegetables•Advantages of pretreatment process for the extraction of cellulose macromolecule•Synthesis and characterization of carboxy-methyl-cellulose with high degree of substitution•CMC based coating formulations on different fruits•Evaluation parameters to determine the efficiency of coating on fruits